‘Reinventing’ agricultural education for 2020 (action programme in the USA) - Juhász, Csaba (Acta Agraria Debreceniensis, 2001)
The world of agricultural education continues to grow more complex. We develop, disseminate and interpret more information in less time than ever before. These rapid changes require new ways of thinking, working and interacting. On January 1, 1996, in the United States of America, The National Council for Agricultural Education inaugurated „Reinventing Agricultural Education for the Year 2020” an initiative to strengthen agricultural and food systems education for the 21st Century. This project is a national effort on behalf of agricultural education, vision and strategic plan for agricultural education in the longer range future. „Reinventing Agricultural Education for the Year 2020” is a visionary planning initiative that brings together key stakeholders at the local, state, regional and national levels. These groups share their thoughts and ideas while developing concensus on what agricultural education should be in the 21st century.